Percutaneous endoscopic drainage for acute long segment epidural abscess following endoscopic lumbar discectomy: A case report - Li, Tao; Wu, Hui; Yuan, Jinghong; Jia, Jingyu; Wu, Tianlong; Cheng, Xigao (Frontiers in Surgery, 2022)
Abstract Introduction: Acute epidural abscess after percutaneous endoscopic lumbar discectomy is a rare but grievous complication. When faced with a long-segment epidural abscess, open surgery has traditionally been performed which can lead to huge surgical trauma and unpredictable complications. For this reason, surgeons around the world are constantly looking for more minimally invasive and effective surgical methods Patient Concerns: Our patient was a 32-year-old woman who had been receiving percutaneous endoscopic interlaminar discectomy for L5/S1 lumbar disc herniation one week ago. She returned to our institution with a fever and lower back pain. Diagnoses: Magnetic resonance imaging revealed a long segment epidural abscess accompanied by a paravertebral abscess, and staphylococcus aureus was detected in a bacterial culture of pyogenic fluids extracted from the paravertebral abscess. Treatments: We performed percutaneous endoscopic drainage (PED) for the epidural abscess. Long-term sensitive antibiotic treatment after surgery. Outcomes: Immediate pain relief was achieved and the inflammatory reaction subsided after 4 weeks of antibiotic therapy. Re-examination of the lumbar spine MRI after 1 month showed that the epidural abscess disappeared completely. Conclusion: Percutaneous endoscopy allowed us to approach the epidural abscess directly, enabling the immediate drainage of the abscess with minimal trauma to the patient. The good results obtained show that percutaneous endoscopic drainage is a reliable way to treat a long-segment epidural abscess.